Pengaruh Rasio Lancar, Margin Laba Bersih Dan Tingkat Pengembalian Asset Terhadap Harga Saham (Studi Pada Perusahaan Index Lq45 Periode 2012-2016) - Setiawati; Nasiruddin; Azizah Indriyani; Amelia Sholeha; Ely Supratin (Universitas Muhadi Setiabudi, 2019)
This study aims to determine: (1) Influence of Current Ratio to Price Stock, (2) Effect of Net Profit Margin on Stock Price, (3) Influence of Return on Assets to Stock Price, (4) Influence of Current Ratio, Net Profit Margin and Return On Assets jointly to Share Price Listed Companies in BEI Period 2012 - 2016. Population in this research is Index LQ45 company which listed in BEI period 2012 - 2016. Sample in this study amounted to 26 companies. Data analysis techniques used is a simple linear regression analysis technique and multiple linear regression analysis. Before the data analysis is done, firstly conducted testing requirements analysis include Test Normality, Linearitas, Multikolinearitas, Autokorelasi, and Heteroskedastisitas. The result of research are: (1) There is negative influence and not significant Current Ratio against Stock Price, (2) There is a positive and significant influence of Net Profit Margin to Stock Price, (3) There is a positive influence and significant Return On Asset on Stock Price, (4) Current Ratio, Net Profit Margin and Return On Asset together have significant effect on Stock Price.